Pelatihan Public Speaking Calon Duta Lingkungan Kolah Banyu di Padukuhan Kroco, Sendangsari, Kulon Progo - Setyaningsih, Emy; Benge, Defaullo Andrean Ronaldino; Primayoga, Alan; Winarno, Joko; Effendi, Tirta Meidival; Setyawan, Imanuel Calvin; Sinaga, Sultoni Wijaya; Lestari, Sisilia Endah (Indonesian Journal of Community Service and Innovation (IJCOSIN), 2025)
Sekolah Sampah Bantala Abyudaya (Kolam Banyu) was established to instill awareness of environmental preservation. Therefore, Kolah Banyu, with its noble goal, needs environmental ambassadors who can speak in public to achieve this. The PPK Ormawa Team of BEM Universitas AKPRIND Indonesia tried to help overcome this problem by holding public speaking training. This training aims to improve the skills and confidence of prospective Kolah Banyu environmental ambassadors. The public speaking training targets PIK-R Mekar Asri Padukuhan Kroco, Sendangsari, Pengasih Kulon Progo, who will later act as environmental ambassadors at Kolah Banyu. Based on the results of the pre-test and post-test, the average pre-test score of participants was 41.62 with a standard deviation of 6.60, while the average post-test score increased to 81.47 with a standard deviation of 6.10. The paired t-test showed a t-statistic of -28.305 and a p-value of 0.000, while the Wilcoxon test gave a statistical value of 0.0 and a p-value of around 1.16e-10. These tests indicate that the training effectively increased knowledge, confidence, and public speaking skills. In addition, no participants experienced a decrease in scores, proving that all participants experienced increased knowledge and skills with a 95% confidence level.